Two Genomic Loci Control Three Eye Colors in the Domestic Pigeon (Columba livia). (30th August 2021) - Maclary, Emily T; Phillips, Bridget; Wauer, Ryan; Boer, Elena F; Bruders, Rebecca; Gilvarry, Tyler; Holt, Carson; Yandell, Mark; Shapiro, Michael D
Abstract: The iris of the eye shows striking color variation across vertebrate species, and may play important roles in crypsis and communication. The domestic pigeon ( Columba livia ) has three common iris colors, orange, pearl (white), and bull (dark brown), segregating in a single species, thereby providing a unique opportunity to identify the genetic basis of iris coloration. We used comparative genomics and genetic mapping in laboratory crosses to identify two candidate genes that control variation in iris color in domestic pigeons. We identified a nonsense mutation in the solute carrier SLC2A11B that is shared among all pigeons with pearl eye color, and a locus associated with bull eye color that includes EDNRB2, a gene involved in neural crest migration and pigment development. However, bull eye is likely controlled by a heterogeneous collection of alleles across pigeon breeds. We also found that the EDNRB2 region is associated with regionalized plumage depigmentation (piebalding). Our study identifies two candidate genes for eye colors variation, and establishes a genetic link between iris and plumage color, two traits that vary widely in the evolution of birds and other vertebrates.